A Method to Determine External Horizontal Overhang Projection Considering the Window Solar Angle Properties in Hot and Humid Climate - Dilshan, Remaz Ossen (Fakulti Alam Bina, UTM, 2006)
A method to determine the optimum overhang projection ratio using total solar energy transmittance (G value) of a window system is presented. The method consists in determining the ideal hourly G value of the window and transmitted heat gains on main cardinal orientations; east, west, north and south. These G-values were utilized to determine the solar radiation intensities for the respective hours of the day. The results were based on the solar radiation data obtained from Subang Meteorological Station, Subang Malaysia, for the year 2001. The results showed that comparison between the window properties and the amount of solar energy transmitted, enable to predict more realistic shading hypothesis than shading device calculations based on incident angle only. The above results suggested optimum overhang ratio of 1.6 (~1.59) for east orientation, overhang ratio between 1.90 and 2.04 for west orientation, overhang ratio between 0.8 and 0.7 for north orientation and between 0.6-0.5 for south orientation. An important benefit of this method is that it gives a series of options of different shading strategies internal or external, to decide based on window systems G-cos value (or solar heat gain coefficient-SHGC) for different orientations.